PENCIPTAAN MANUSIA DALAM SURAT AL-MU’MINUN AYAT 12,13 DAN 14: (Kajian Tafsir Al-jawahir fi Tafsir Al-Qur’an Al-Karim Karya Shaykh Tantawi Jawhari) - Andressa Muthi' Latansa (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
The discourse of this research relates to the verse on the creation of humans in the interpretation of the QS. Al-Mu'minu>n verses 12-14 interpretation of Tantawi Jawhari> with his interpretation which tries to contextualize the text withthe current conditions by using a scientific interpretation approach. So that it raises positive implications that are axiological or applicable that the verses of the Qur'an have continuity in providing instructions for humans which are packaged in a relevant language. And also negative implications, which lead to misunderstandings regarding the verses of mubham, muhkam, mutasyabihat; it is as if the Qur'an came down in relation to events that are happening, even though not all of the verses are like that; and the religious values of the Koran are reduced.